Construction and sequencing of an infectious clone of the goose embryo-adapted Muscovy duck parvovirus vaccine strain FZ91-30 - Wang, J. Y.; Huang, Y.; Zhou, M. X.; Hardwidge, Philip R.; Zhu, G. Q. (My University, 2016)
Background: Muscovy duck parvovirus (MDPV) is the etiological agent of Muscovy duckling parvoviral disease, which is characterized by diarrhea, locomotive dysfunction, stunting, and death in young ducklings, and causes substantial economic losses in the Muscovy duck industry worldwide. FZ91-30 is an attenuated vaccine strain that is safe and immunogenic to ducklings, but the genomic information and molecular mechanism underlining the attenuation are not understood. Methods: The FZ91-30 strain was propagated in 11-day-old embryonated goose eggs, and viral particles were purified from the pooled allantoic fluid by differential centrifugation and ultracentrifugation. Single-stranded genomic DNA was extracted and annealed to form double-stranded DNA. The dsDNA digested with NcoI resulted two sub-genomic fragments, which were then cloned into the modified plasmid pBluescript II SK, respectively, generating plasmid pBSKNL and pBSKNR. The sub-genomic plasmid clones were sequenced and further combined to construct the plasmid pFZ that contained the entire genome of strain FZ91-30. The complete genome sequences of strain FM and YY and partial genome sequences of other strains were retrieved from GenBank for sequence comparison. The plasmid pFZ containing the entire genome of FZ91-30 was transfected in 11-day-old embryonated goose eggs via the chorioallantoic membranes route to rescue infectious virus. A genetic marker was introduced into the rescued virus to discriminate from its parental virus. Results: The genome of FZ91-30 consists of 5,131 nucleotides and has 98.9 % similarity to the FM strain. The inverted terminal repeats (ITR) are 456 nucleotides in length, 14 nucleotides longer than that of Goose parvovirus (GPV). The exterior 415 nucleotides of the ITR form a hairpin structure, and the interior 41 nucleotides constitute the D sequence, a reverse complement of the D' sequence at the 3' ITR. Amino acid sequence alignment of the VP1 proteins between FZ91-30 and five pathogenic MDPV strains revealed that FZ91-30 had five mutations; two in the unique region of the VP1 protein (VP1u) and three in VP3. Sequence alignment of the Rep1 proteins revealed two amino acid alterations for FZ91-30, both of which were conserved for two pathogenic strains YY and P. Transfection of the plasmid pFZ in 11-day-old embryonated goose eggs resulted in generation of infectious virus with similar biological properties as compared with the parental strain. Conclusions: The amino acid mutations identified in the VP1 and Rep1 protein may contribute to the attenuation of FZ91-30 in Muscovy ducklings. Plasmid transfection in embryonated goose eggs was suitable for rescue of infectious MDPV.
Citation: Wang, J. Y., Huang, Y., Zhou, M. X., Hardwidge, P. R., & Zhu, G. Q. (2016). Construction and sequencing of an infectious clone of the goose embryo-adapted Muscovy duck parvovirus vaccine strain FZ91-30. Virology Journal, 13, 8. doi:10.1186/s12985-016-0564-9
Keywords: Muscovy Duck Parvovirus; Attenuation; Infectious Clone; Rescue; Transfection; Waterfowl Parvoviruses